Clinical factors associated with growth and neoantigen reactivity of tumor infiltrating lymphocytes from metastatic epithelial cancers - Alexandra M. Gustafson; Aaron J. Dinerman; Kyle J. Hitscherich; Maria R. Parkhurst; Hyunmi Halas; Donald E. White; Chuong D. Hoang; Jonathan M. Hernandez; Mei Li M. Kwong; Nicholas D. Klemen; Steven A. Rosenberg; Stephanie L. Goff; et al. (Cancer Immunology, Immunotherapy)
Abstract Background Adoptive cell therapy with tumor infiltrating lymphocytes is FDA approved for metastatic melanoma. TIL from patients with melanoma and factors relating to growth and reactivity have been studied; however, this has not been explored in patients with epithelial cancers. Patients and methods Metastatic epithelial tumors resected for TIL growth from 2014 to 2023 were analyzed. Two hundred and ninety-one operations were performed to collect TIL for potential treatment. Of these, 263 harvests were each processed for up to 24 individual fragment cultures and screened for neoantigen recognition of the expressed products of cancer mutations. Patient and tumor characteristics were collected. Endpoints were growth (defined as more than half of all fragment cultures expanded for viable cryopreservation) and patient-specific neoantigen reactivity (release of interferon-γ in cocultures measured by ELISpot and 4-1BB upregulation on flow cytometry). Results TIL fragments reached adequate growth for screening by 21 days. Metastatic resections from lung were more likely to grow TIL than all other resection sites combined (95%, p = 0.0011), while hepatic resections were less likely to grow (69%, p < 0.0001). One hundred and thirty-five patients (51%) had highly reactive TIL, 68 (26%) had weakly reactive TIL, and 60 (23%) had TIL with no neoantigen reactivity. Patients with prior exposure to immune checkpoint blockade therapy were less likely to have highly reactive TIL (p = 0.0325). Metastatic resection site impacted TIL reactivity against neoantigens, with those harvested from the lung more likely to show any reactivity (83%, p = 0.0180), as well as high reactivity (59%, p = 0.0066). Conclusions Prior immune checkpoint therapies reduced the likelihood of having highly reactive TIL. Neoantigen reactivity was more common in TIL from thoracic resections versus other sites. Conversely, hepatic lesions yielded TIL less likely to grow and with less reactivity. These results contribute to improved strategies for sequencing TIL with other therapies and planning TIL harvests for patients with epithelial cancers.